Mednarodna historična sociologija kapitalistične modernosti - Rutar, Tibor (Družboslovne razprave, 2016)
The project of International Historical Sociology - a synthesis of Historical Sociology and International Relations - which has been in accelerated development for the past two decades, emerged out of a double analytical impasse: that of sociological reductionism ("methodological internalism") and international reductionism ("methodological externalism"), and that of Eurocentrism. The article evaluates the broader benefits and pitfalls of this project by critically examining some of the key theoretical and empirical theses in the recent literature; special attention is given to the praised and exemplifying work How the West Came to Rule. We show that the paradigm of "Political Marxism" avoids methodological internalism and Eurocentrism in theorising the emergence and spread of capitalist modernity, while the acclaimed alternative paradigm of "Uneven and Combined Development" does not introduce new explanatory insights to this theorisation and is, in some respects, even less satisfactory.
Keywords: Historical sociology; Zgodovinska sociologija; Mednarodni odnosi; International relations; Marksizem; Marxism; kapitalizem; capitalism